Images in the making Art, process, archaeology - Back Danielsson, Ing-Marie; Meirion Jones, Andrew (Manchester University Press, 2020)
This book presents a study of material images and asks how an appreciation of the making and unfolding of images and art alters archaeological accounts of prehistoric and historic societies. With contributions focusing on case studies including prehistoric Britain, Scandinavia, Iberia, the Americas and Dynastic Egypt, and including contemporary reflections on material images, it makes a novel contribution to ongoing debates relating to archaeological art and images. The book offers a New Materialist analysis of archaeological imagery, with an emphasis on considering the material character of images and their making and unfolding. The book reassesses the predominantly representational paradigm of archaeological image analysis and argues for the importance of considering the ontology of images. It considers images as processes or events and introduces the verb 'imaging' to underline the point that images are conditions of possibility that draw together differing aspects of the world. The book is divided into three sections: 'Emergent images', which focuses on practices of making; 'Images as process', which examines the making and role of images in prehistoric societies; and 'Unfolding images', which focuses on how images change as they are made and circulated. The book features contributions from archaeologists, Egyptologists, anthropologists and artists. The contributors to the book highlight the multiple role of images in prehistoric and historic societies, demonstrating that archaeologists need to recognise the dynamic and changeable character of images.